Web-based Professional Development for Improving Early Childhood Professionals' Actual and Perceived Knowledge of Dual Language Learners. Issue 4 (1st October 2020) - Gardner-Neblett, Nicole; Franco, Ximena; Mincemoyer, Claudia; Morgan-Lopez, Antonio A.
ABSTRACT: Web-based professional development has the potential to increase the early childhood workforce's knowledge of young dual language learners (DLLs). Yet there is a gap in the literature on web-based professional development specific to DLLs and its role in changes in actual and perceived knowledge among early childhood professionals. To begin addressing this gap, the current study examines the associations between early childhood professionals' participation in a web-based learning platform with targeted content on supporting young DLLs and changes in actual and perceived knowledge about DLLs. This study also examines how background characteristics and experiences may be associated with increases in knowledge after module participation. Results show increases in participants' actual and perceived knowledge after completing the module. Relevant background characteristics included having a college-degree, working in home-based child care, and participating in DLL-specific professional development within the prior year. Having prior DLL-specific professional development moderated the links between pre-module knowledge and post-module knowledge. These results highlight the relevance of web-based professional development as an approach to building the knowledge of early childhood professionals to work with young DLLs.